Metaphor in the discourse of the Conservative Party in the United Kingdom. - Krawczak, Marcin (Investigationes Linguisticae, 2010)
Politics remains one of the most essential domains of social life and therefore has a great impact on people’s conceptualization of leadership and the values it strives to transfer to its potential advocates. This paper aims to explore mechanisms of metaphor assortment undertaken by politician-speakers by examining the individual attributes as orators and the properties of their audiences of three Conservative leaders: Churchill, Thatcher and Cameron during their public service, taking into account ancient views on the art of persuasion.